Aspectos clínicos e biomecânicos associados à discinese escapular de indivíduos com e sem síndrome do impacto subacromial - Gonçalves, Diogo Henrique Magalhães (2019)
Introduction: Shoulder pain is one of the main complaints of pain in the general population, with subacromial impact syndrome (SIS) being the most prevalent painful condition, about 44% to 65% in this population, being more prevalent in young women. Its etiology is considered multifactorial, among the main alterations described in the literature are motor control, weakness of the periescapular musculature, consequently it can generate kinematic changes in the scapula and scapulothoracic and glenohumeral biomechanical disturbance, being scapular dyskinesis the main factor. Associating the SIS with the kinematic changes of the scapula has been studied worldwide, however, it is not clear how much these changes influence the onset of SIS. Although there may be a direct relationship between them, we have no support in the literature to state whether abnormal scapular movement predicts this condition or whether pain intensity produces variability in scapulothoracic movements according to the function or task performed. In addition, even if changes in muscle activity and strength deficit in periescapular muscles are present in individuals with SIS, as well as the scapular dyskinesis can be present in this population, it is unclear if using these factors as predictors for this shoulder condition. Objectives: 1. To compare the electromyographic activity and strength of the periescapular and shoulder muscles during arm flexion and abduction movements in participants with and without SIS and scapular dyskinesis divided into subgroups. Methods: 1. Cross-sectional study evaluating the strength and electromyography of 117 participants divided into subgroups, 20 No Pain + No Scapular Dyskinesis (SDK), 26 Pain + Scapular Dyskinesis (SDK), 41 No Pain + Scapular Dyskenesis (SDK) and 30 Pain + No Scapular Dyskinesis (SDK) during arm abduction and flexion movement. Strength and EMG data were analyzed using MANOVA, the significance level was set at (P <0.05). A cross-sectional study with 117 participants, 61 in the control group and 57 in the SIS group, all underwent three-dimensional kinematic evaluation during arm flexion and abduction movements. Results: 1. Comparing groups during arm flexion and abduction movements in the arm up and down phases, there are no differences in Upper Trapezius (UT), Middle Trapezius (MT), Lower Trapezius (LT), Serratus Anterior (SA), Abductors at 90 degrees (ABD90°), Adductors at 90 degrees (ADD90°), Lateral Rotators (LR) and Medial Rotators (MR) [F = 1,320; p> 0.05; Wilk λ = 0.755] and EMG of Biceps Brachii (BB), Anterior Deltoid (AD), Middle Deltoid (MD), Posterior Deltoid (PD), Upper Trapezius (UT), Middle Trapezius (MT), Lower Trapezius (LT) and Serratus Anterior (SA) in abduction [F = 0.883; P> 0.05; Λ = 0.826] and flexion [F = 0.956; P> 0.05; Λ = 0.813] of Wilk between the groups, suggesting that the muscle strength and activity variable has no direct relationship with SIS and scapular dyskinesis. Comparison of biopsychosocial questionnaires between groups showed differences (P <0.05) for SPADI, QuickDASH, TAMPA and B-PCS indicating that these factors may influence the biomechanical behavior of these individuals. Conclusion: 1. Based on the findings of this research and the evidence found in the literature, we can suggest that the arrangement of participants in groups may help to better understand the shoulder condition regarding SIS and scapular dyskinesis. Objectives: 2. To compare the scapula, humerus and trunk kinematics in participants with and without SIS during the arm up and down phase during flexion and abduction movements. Methods: 2. A cross-sectional study with 117 participants, 61 in the control group and 57 in the SIS group, all underwent three-dimensional kinematic evaluation during arm flexion and abduction movements. The kinematic data were analyzed using the vector field, to identify the differences throughout the movement cycle. The results entered in the form of graphs with the Statistical Parametric Mapping (SPM). Results: 2. The kinematic variables showed differences of lower upward rotation, greater internal rotation and lower posterior scapular inclination, greater trunk lateral extension and inclination, and greater humerus flexion when compared to GSIS during the abduction movement in up and down phase. In the arm flexion movement, the kinematic differences were smaller upward rotation and posterior inclination of the scapula. There was no statistical difference (P> 0.05) for trunk variables. In the humerus there was less internal rotation, this statistical difference was found when comparing the Group Subacromial Impingement Syndrome (SIS) and Control Group (GC). Conclusion: 2. These kinematic changes found in the scapula, humerus and trunk show that we must consider the evaluation of these segments in different planes, the statistical analysis provided new information of this evaluation, as well as another way to interpret these data.